Sustainability assessment for biodiesel production via fuzzy optimisation during research and development (R&D) stage - Liew, Weng Hui (Springer, 2014)
Biodiesel is regarded as an important renewable fuel for meeting the global future energy demand and resolving the environmental problems (e.g. global warming). Despite its known advantages, it is still very critical to assess the sustainability of biodiesel production prior to greater expansion for commercialisation. Early hazard assessment when the process is still under development and design is very beneficial as process modifications to eliminate or reduce hazards can be made easier at lower costs. In this paper, inherent safety, health and environment (SHE) and economic performance (EP) analysis is conducted for biodiesel production during the earliest process lifecycle which is named as research and development (R&D) stage. Prior to the assessment, eight biodiesel production pathways via base-catalysed, acid-catalysed, enzymatic and supercritical transesterification using fresh or waste oil are classified. The inherent SHE assessments are conducted using the renowned methods of the Prototype Index of Inherent Safety (PIIS), Inherent Occupational Health Index (IOHI) and Inherent Environmental Toxicity Hazard (IETH) for inherent safety, health and environmental friendliness, respectively. The EP assessment is done using a proposed costing assessment based on operating cost and revenue. A systematic framework for assessing alternative biodiesel production pathways during the R&D stage is presented. Fuzzy optimisation approach is used to assess the pathway candidates based on multiple objectives of inherent SHE and EP. From the assessment result, it is found that biodiesel production based on enzymatic transesterification using waste oil is the most desirable pathway. Following the result of the assessments, several improvement actions for inherent SHE in biodiesel production are proposed and discussed.